Cycloelimination-assisted Combinatorial Synthesis of Diverse Heterocyclic Scaffolds of Chemotherapeutic Values - Prasad, Virendra; Mishra, Nidhi; Agrahari, Anand K.; Singh, Sumit K.; Mohapatra, Prabhu P.; Tiwari, Vinod K. (Current Organic Chemistry, 2019)
Recent advances in high-throughput, automated techniques combined with the identification of new therapeutic targets in genome sequencing and molecular biology have generated a need for a large collection of diverse heterocyclic scaffolds. This inspires toward the development of novel reaction sequences and linking strategies to generate libraries of diverse simple to complex heterocyclic systems. In this regard, combinatorial chemistry has emerged as an excellent technology platform for the rapid assembly of building blocks to synthesize complex molecular structures with great ease in a few synthetic steps. By means of the implementation of high-throughput screening for the biological evaluation of hits and leads, combinatorial libraries have become important assets in drug discovery and development. In the last two decades, the cyclorelease strategy that minimizes the chemical and tethering implications by releasing the intact desired target molecule in the final step of reaction has attracted much attention. Recently, a particular interest is developing in linking strategies, where loading and cleavage steps contribute to the complexity of the target structure rather than only extraneous manipulations. This review summarises the practical and high-yielding approaches of solid phase combinatorial synthesis for diverse high-purity heterocyclic skeletons of pharmacological importance involving the cycloelimination strategy.
Keywords: solid phase synthesis